Efektivitas Pelaksanaan Program Pemberdayaan dan Kesejahteraan Keluarga di Kelurahan Pagentan Kecamatan Singosari Kabupaten Malang - Madhaniyah Nur Purnamasari; Sunariyanto; Septina Dwi Rahmawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research explores the optimization of the performance efforts of the village government in providing public services in Kuwolu Village, Bululawang Sub-district. The main focus of the research is on the adoption of technology, responsiveness to changes in societal values, the implementation of Law Number 25 of 2009 concerning Public Services, and community participation. The research findings indicate that the adoption of technology has a positive impact on improving administrative efficiency, although challenges related to digital literacy still need to be addressed. Being responsive to changes in societal values is a critical point in formulating service policies that align with local expectations. Law Number 25 of 2009 provides clear direction, but its implementation requires in-depth understanding and adjustment to local conditions. Improving service quality and administrative efficiency remains the primary focus, with active community participation as a vital instrument. Cross-sectoral collaboration and institutional cooperation are identified as assets to create synergy in service provision. Inclusive measures through training programs and digital literacy serve as solutions to address disparities and unequal access. This research paints a picture of the performance efforts of the village government in facing the dynamics of public service in the era of digital transformation and changing societal values. It is hoped that these findings can guide other village governments in creating an effective and responsive public service system amid the challenges of the times.